Contingent protection as better insurance - Thomas J. Prusa; Ronald D. Fischer (Rutgers University, Department of Economics, 1999)
We formalize the notion that GATT exceptions such as antidumping and escape clause actions can act as insurance for import competing sectors affected by adverse price shocks. We use a general equilibrium model with several import competing sectors and assume incomplete markets so that agents cannot contract insurance. We show that these measures are superior to uniform tariffs as insurance mechanisms. Moreover, we demonstrate that the optimal uniform policy may involve a tariff at all, but rather might entail an export tax. We also show that a tax cum subsidy policy (i.e., taxing all sectors in order to subsidize the shocked sector) improves welfare.
Keywords: F13; 330; antidumping; contingent protection; insurance